A case report of intrahepatic bile duct confluence anomalies in VACTERL syndrome. Issue 39 (September 2018) - Yoon, Yoonsun; Kim, Kyungju; Yeom, Suk Keu; Lee, JeeHyun; Lee, Yoon
Abstract: Rationale: The clinical manifestations of VACTERL association include vertebral anomalies, anal atresia, congenital heart diseases, tracheoesophageal fistula, renal dysplasia, and limb abnormalities. The association of intrahepatic anomalies and VACTERL syndrome is a rare coincidence. VACTER syndrome and intrahepatic bile drainage anomalies might be genetically related. Patient concerns: A 12-year-old girl presented with episodic colicky abdominal pain, nausea, and vomiting for several years. The individual episodes resolved spontaneously within a few days. She had a history of VACTERL syndrome, including a butterfly shape of the L3 vertebra, anal atresia, and an atrial septal defect. Diagnoses: On laboratory findings, abnormal liver function tests included elevated total bilirubin, alanine aminotransferase, aspartate aminotransferase, and gamma-glutamyltransferase. There was no significant abnormal finding in hepatobiliary system sonography except mild gallbladder wall thickening. We performed magnetic resonance cholangiopancreatography and demonstrated an abnormal intrahepatic bile duct confluence, which showed 3 bile ducts draining directly into the neck of the gallbladder. Intervention: Her symptoms related to bile reflux during gallbladder contraction. Cholecystectomy with choledochojejunostomy was undertaken because segments of the bile drainage were intertwined. Outcomes: After surgery, her symptoms decreased, but abdominal discomfort remained due to uncorrected left intrahepatic anomalies. Lessons: Although hepatobiliary anomalies are not included in VACTERL association diagnostic criteria, detailed hepatobiliary work up is needed when gastrointestinal symptoms are present in VACTERL association patients.